Study of single mode tapered fiber-optic interferometer of different waist diameters and its application as a temperature sensor - Yadav, T. K.; Mustapa, Mohd Azmir; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir (European Optical Society, 2014)
We have proposed a study on single-mode tapered optical fiber for temperature sensing application. A theoretical analysis and its experimental validation were carried out to study the taper profile for highly sensitive temperature sensor. Experiments were performed to observe a wavelength shift of transmission spectra with different taper profiles. The effects of taper profiles on the sensitivity of the sensor were also investigated. Our results indicate that the tapered fiber-based temperature sensor has sensitivity in the range of 0.01143 to 0.03406 nm/C. The findings also demonstrate that the sensor sensitivity can be adjusted with variation to the taper profile.